Telerehabilitation for Lung Transplant Candidates and Recipients During the COVID-19 Pandemic: Program Evaluation - Lisa Wickerson; Denise Helm; Chaya Gottesman; Dmitry Rozenberg; Lianne G Singer; Shaf Keshavjee; Aman Sidhu (JMIR Publications, 2021)
BackgroundThe COVID-19 pandemic resulted in a rapid shift from center-based rehabilitation to telerehabilitation for chronic respiratory disease and lung transplantation due to infection control precautions. Clinical experience with this delivery model on a large scale has not been described. ObjectiveThe aim of this study is to describe usage and satisfaction of providers and lung transplant (LTx) candidates and recipients and functional outcomes following the broad implementation of telerehabilitation with remote patient monitoring during the first wave of the COVID-19 pandemic. MethodsThis study was a program evaluation of providers, LTx candidates, and early LTx recipients who used a web-based, remote monitoring app for at least four weeks between March 16 and September 1, 2020, to participate in telerehabilitation. Within-subjects analysis was performed for physical activity, Self-efficacy For Exercise (SEE) scale score, aerobic and resistance exercise volumes, 6-minute walk test results, and Short Physical Performance Battery (SPPB) results. ResultsIn total, 78 LTx candidates and 33 recipients were included (57 [51%] males, mean age 58 [SD 12] years, 58 [52%] with interstitial lung disease, 34 [31%] with chronic obstructive pulmonary disease). A total of 50 (64%) LTx candidates and 17 (51%) LTx recipients entered ≥10 prescribed exercise sessions into the app during the study time frame. In addition, 35/42 (83%) candidates agreed the app helped prepare them for surgery and 18/21 (85%) recipients found the app helpful in their self-recovery. The strongest barrier perceived by physiotherapists delivering the telerehabilitation was patient access to home exercise and monitoring equipment. Between the time of app registration and ≥4 weeks on the waiting list, 26 LTx candidates used a treadmill, with sessions increasing in mean duration (from 16 to 22 minutes, P=.002) but not speed (from 1.7 to 1.75 mph, P=.31). Quadriceps weight (pounds) for leg extension did not change (median 3.5, IQR 2.4-5 versus median 4.3, IQR 3-5; P=.08; n=37). On the Rapid Assessment of Physical Activity questionnaire (RAPA), 57% of LTx candidates scored as active, which improved to 87% (P=.02; n=23). There was a decrease in pretransplant 6-minute walk distance (6MWD) from 346 (SD 84) meters to 307 (SD 85) meters (P=.002; n=45) and no change in the SPPB result (12 [IQR 9.5-12] versus 12 [IQR 10-12]; P=.90; n=42). A total of 9 LTx recipients used a treadmill that increased in speed (from 1.9 to 2.7 mph; P=.003) between hospital discharge and three months posttransplant. Quadriceps weight increased (3 [IQR 0-3] pounds versus 5 [IQR 3.8-6.5] pounds; P<.001; n=15). At three months posttransplant, 76% of LTx recipients scored as active (n=17), with a high total SEE score of 74 (SD 11; n=12). In addition, three months posttransplant, 6MWD was 62% (SD 18%) predicted (n=8). ConclusionsWe were able to provide telerehabilitation despite challenges around exercise equipment. This early experience will inform the development of a robust and equitable telerehabilitation model beyond the COVID-19 pandemic.